Proposals to handle the new online classes modality and its effects on the intrinsic motivation of the second-year students of the modern languages degree of the School of Sciences and Arts of the University of El Salvador taking the course intermediate intensive english ll in 2021. - Molina Cruz, Rafael Alberto; Suria Barrera, Álvaro Daniel (2024)
The following research study addressed the topic of students' intrinsic motivation and how it was affected by the new online classes modality caused by the COVID-19 pandemic where areas such as the academic output, motivation, self-esteem, participation in classes, and attendance were impacted and consequences such as Irregular Attendance and Willingness to Participate in Class were discovered. Also, the research presented different existing techniques, such as Constructivism, Gamification, Collaborative Learning, as alternative to address the new classes modality and prosed an idea to handle it and the effects on the intrinsic motivation. The importance of this research lies in its immediate effect on how students have been affected in their academic output and how to counteract it using a proposal made by the research team using all the information gathered within the research. This proposal can be used by the Foreign Language Department as an idea to continue with the online classes modality as an alternative option.